Investigating the role of student teams-achievement divisions (STAD) on Saudi undergraguates’ motivation and vocabulary - Fazal, Muhammad Ishtiaq (2019)
This study investigates the effects of Student Teams-Achievement Divisions (STAD) on Saudi undergraduates’ motivation in learning L2 vocabulary. It also explores Saudi undergraduates’ views about STAD as a strategy that can enhance their motivation in learning vocabulary. The current study used a sequential explanatory design. It was held at Unaizah Community College, Qassim University, Saudi Arabia. Two intact groups were selected from the first semester as STAD group and Traditional Learning group. Seventy six students (N=38 in each group) participated in the study. The STAD group was taught with Student Teams-Achievement Divisions (STAD) for eight weeks. The TL group was taught with traditional teacher-fronted method for the same period of time. A motivation questionnaire and a vocabulary test were administered before and after the intervention in the first phase. The quantitative data was analyzed using one way ANOVA. In the follow up phase, some students from the STAD group and the TL group were contacted for open ended interviews. The interviews were analyzed using ATLAS ti. The results of the motivation questionnaire, the vocabulary test and the interviews suggest that STAD is an effective strategy for teaching English to Saudi undergraduates. The STAD group significantly outperformed the TL group in the motivation questionnaire and the vocabulary test. The mean score of the STAD group is higher than the mean score of the TL group on the post-questionnaire and the vocabulary test. Qualitative data also suggests that Saudi undergraduates view STAD as a strategy that can enhance their motivation in learning vocabulary. The findings of the current study support social interdependence theory. According to this theory, learners work together, cooperate, show social competence and make psychological adjustments to be successful. Learners feel that their actions are important for their groups. This motivates them to learn and help others to learn. The findings of the current study will have important pedagogical implications in EFL context. EFL teachers may apply different CL strategies in their classrooms to give their students different learning experiences. An important theoretical implication that can be drawn from the findings is the value of social and cognitive development of students. Findings of the current study suggest that a cooperative learning experience can improve students’ social and cognitive development.